PENGARUH LEVERAGE, FINANCIAL DISTRESS DAN LIQUIDITY SEBAGAI PENGAMBILAN KEPUTUSAN HEDGING (Studi Kasus pada Perusahaan yang Terdaftar pada Bursa Jakarta Islamic Index Periode 2011-2015) - Fatimia, Al; Sulhan, Muhammad (IQTISHODUNA, 2016)
Hedging is one alternative risk management to protect the assets of the company resulting from theforeign exchange risk. Hedging by using derivative instrumentis common ways that is used by the company.This study aimed to determine the effect of leverage, and liquidity of financial distress, both simultaneouslyand partially to the company’s decision to do hedging. The population in this study was a company in JakartaIslamic Index on the observation period of 2011-2015. The sampling technique used in this research waspurposive sampling method in order to obtain a sample of seven companies. The techniques in this studyused multiple regression analysis software of SPSS version 16. The results of this study that of the fourvariables used, there was one variable that affected the company to be used as a hedging decision making.Variable that affected the hedging activities was the current ratio, because if the value of the current ratio washigh then indicated that the liquid assets that was managed by the company was also high, so it needed toimplement a policy of hedging, quick ratio was getting the negative and significant, which meant that if thevalue of the variable quick ratio was low, then the company pushed for hedging, debt to equity ratio had nosignificant effect on hedging, this was because the company was using the rupiah currency to do debt,financial distress had no significant because the company was not experiencing the financial difficulties.